Pengaruh pH Pada Proses Hidrolisis Mikro Alga Chlorella Vulgaris Menjadi Glukosa Menggunakan Enzim Selulase - Windy Odelia Putri; Amun Amri; Syelvia Putri Utami (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Microalgae is one of the organisms can be considered as ideal and potential raw material for production of biofuels. Chlorella Vulgaris is a group of green algae that have prospect to be developed. The purpose of this research was to find the effect of pH to enzymatic hydrolysis and obtain the optimum glucose concentration on enzymatic hydrolysis on microalgae Chlorella Vulgaris. Hydrolysis was performed with the variated the conditions of pH was 5, 6, and 7 respectively. Microalgae Chlorella vulgaris was diluted using buffer citrat acid and then mixed with cellulase enzyme. Hydrolysis process was carried out for 48 hours at 100 rpm agitation. Result of experiment was tested by using spectrofotometry UV-VIS. The results showed that the increasing of pH will increased the glucose concentration until optimum condition. The optimum glucose concentration was5,35g/L at pH 6.Keyword: cellulase, chlorella vulgaris, enzymatic, glucose, pH.